Production of mannose-containing oligosaccharides by glucansucrase E81 and determination of their functional characteristics - Ispirli, Humeyra; Dertli, Enes (TAYLOR & FRANCIS LTD, 2020)
Oligosaccharides are one of the functional ingredients to be used in food technology. In this study, by using an active glucansucrase GTFA-Delta N E81 in the acceptor reaction of mannose, mannose-containing oligosaccharides were produced and their functionality was tested. The formation of the oligosaccharides were visualised by TLC analysis and mannose-containing oligosaccharides up to DP 7 were determined by LC-MS analysis. The presence of the (1,6)Glc and (1,3)Glc units within the oligosaccharides were determined by NMR analysis. The in vitro immune-modulatory functions of the mannose-containing oligosaccharides were determined but no induction in IL-4, IL-10, IL-12 and TNF-alpha cytokine levels were detected. Importantly this oligosaccharide mixture showed prebiotic effect by triggering the growth of tested probiotics and not affecting the growth of pathogen strains. Our findings reveals the potential of the role of glucansucrases for the production of functional oligosaccharides.
Keywords: Glucansucrase; mannose-containing oligosaccharides; immune modulation; prebiotic; PREBIOTIC PROPERTIES; FECAL MICROFLORA; MANNOOLIGOSACCHARIDES; POLYSACCHARIDE; COFFEE; DIGESTIBILITY; FERMENTATION; MODULATION; MICROBIOTA; GALACTOSE; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology